Microbial community distribution in variously altered basalts: Insights into astrobiology sample site selection. (December 2020) - Brady, Allyson L.; Gibbons, Erin; Sehlke, Alexander; Renner, Caleb J.; Kobs Nawotniak, Shannon E.; Lim, Darlene S.S.; Slater, Greg F.
Abstract: Terrestrial basalts represent ecological niches with the potential for microbial habitability. However, little is known about how gradients of physical and/or chemical alteration may impact the distribution of microbial biomass. If higher abundances of microbial biomass are associated with identifiable alteration features, i.e. visible from orbit or rover, such features would become an important tool in the selection of astrobiology targets for future life-detection missions. To examine the associations between biomass abundance and basalt alteration processes, phospholipid fatty acid (PLFA) biomarker analysis was used to assess microbial biomass in basalts representative of distinct alteration categories collected from two Mars analog environments: Craters of the Moon National Monument and Preserve (COTM), Idaho and Hawai'i Volcanoes National Park (HVNP), Hawai'i. PLFA concentration was generally highest in field categorized high-temperature alteration (syn-emplacement) samples within COTM, particularly in those that may have also undergone some degree of secondary weathering. Basalts from HVNP showed more variable biomass abundances, with no clear trend between altered and unaltered basalts. HVNP fumarolic deposits (both active and relict fumarole-associated samples) generally had consistently detectable biomass although temperature appeared to play a role in abundance with the highest temperate fumarole exhibiting the lowest PLFA concentration. PLFA profiles generally had high proportions of brPLFA (including biomarkers of iron- and sulfur-reducing bacteria) and indicated that basalts were dominated by heterotrophic organisms, however no clear trend between community biomarker composition and alteration type or extent was identified. Heterogeneity of microbial biomass within terrestrial basalts suggests that identification of distinct alteration features clearly linked to high biomass (biomarkers) is challenging but that altered materials (syn-emplacement and secondary weathering) and fumarolic deposits are likely promising astrobiology targets. Highlights: Terrestrial basalts contain detectable levels of microbial phospholipid fatty acids. Texture and mineralogy may play a role in biomass abundance. Altered basalts have higher biomass than unaltered material. Variation in microbial community between locations but less so within flows. Syn-emplacement basalts with secondary weathering potential astrobiology targets.